NRT1.1-Mediated Nitrate Suppression of Root Coiling Relies on PIN2- and AUX1-Mediated Auxin Transport - Chai, Sen; Li, En; Zhang, Yan; Li, Sha (Frontiers in Plant Science, 2020)
Asymmetric root growth (ARG) on tilted plates, or root coiling on horizontally-placed plates, is proposed to be a combination of gravitropism, mechanical sensing, and circumnutation, a word designated by Charles Darwin to describe the helical movement that all plant organs make around the growth direction. ARG is developmentally controlled in which microtubule-regulating proteins and the phytohormone auxin participates. Nutrient deficiency influences ARG. However, it is unclear which nutrients play key roles in regulating ARG, what endogenous components are involved in responding to nutrient deficiency for ARG, and how nutrient deficiency is translated into endogenous responses. We report here that nitrate deficiency resulted in a strong ARG in Arabidopsis. Nitrate deficiency caused root coiling on horizontal plates, which is inhibited by an auxin transport inhibitor, and by mutations in PIN-FORMED2 (PIN2) and AUXIN RESISTANT 1 (AUX1). We further show that suppression of ARG by nitrate is mediated by the nitrate transporter/sensor NRT1.1. In addition, PIN2-and AUX1-mediated auxin transport is epistatic to NRT1.1 in nitrate deficiency-induced ARG. This study reveals a signaling pathway in root growth by responding to exogenous nitrate and relaying it into altered auxin transport.